The characteristics of riddle related to the food culture of the Mongols - Chuluun, Zayasuren (Studia Folclorica, 2024)
This article highlights the unique artistic imagery found in riddles based on the five exquisite traditional foods and beverages that are an integral part of Mongolian culture. The knowledge and experience gained from understanding the distinctive aspects of Mongolian food culture are reflected in the depiction of folk riddles. Through the art of words, Mongolians have passed this knowledge down to their children, teaching and preparing them for everyday life. In this type of riddle, the five types of livestock and their body parts are metaphorically represented and vividly illustrated, reflecting the activities, customs, and mindset of herders. Examples demonstrate how these riddles serve as an expression of nomadic life. Word-based arts, including riddles, are a classic example of Mongolian folk wisdom. They preserve and transmit practical knowledge about daily life and livestock identification across generations, ensuring that future generations understand and embrace their cultural heritage. Монголчуудын идээ ундааны соёлд холбогдох оньсогын уран дүрслэлийн онцлог Хураангуй: Энэхүү өгүүлэлд монголчуудын соёлын нэгэн хэсэг болсон таван тансаг идээ ундаагаар бүтсэн оньсогын уран дүрслэлийн онцлогийг тодруулав. Монголчуудын идээн ундааны соёлын онцлогийг таньж мэдсэн арга, туршлага нь монгол ардын оньсогын дүрслэлд тусгалаа олжээ. Үүнийгээ үгийн урлагаар дамжуулан үр хүүхдэдээ заан сургаж, ахуй амьдралд бэлтгэж үлгэрлэн сургаж иржээ. Энэ чиглэлийн оньсогод таван хошуу мал, түүний эд эрхтэнтэй адилтаж, амьдчилан дүрсэлсэн нь малчин хүний үйл ажиллагаа, ёс заншил сэтгэлгээний илрэл болж байгааг жишээгээр харуулсан болно. Түлхүүр үг: цагаан идээ, бор идээ, шар идээ, ногоон идээ, улаан идээ, адилтгал, зүйрлэл, хүншүүлэл, амьдчилал, дүр дүрслэл